Factors comprehensively influencing acceptance of 3D-printed apparel. Issue 2 (8th May 2017) - Perry, Anna
Abstract : Purpose: The purpose of this paper is to incorporate an extended technology acceptance model (TAM) and examine how various factors comprehensively influence and determine consumers' perceptions, attitude, and usage intention of 3D-printed apparel. Design/methodology/approach: An online survey was designed using established measures and 1, 002 participants were recruited. Findings: All external variables were related. Beyond indirect influences, tech optimism still moderately influenced ease of use, but weakly influenced attitude; aesthetics still strongly influenced usefulness and attitude, but weakly influenced usage intention; performance still strongly influenced ease of use, usefulness, and attitude. In addition, only indirect influences came from tech optimism to usefulness and usage intention, aesthetics to ease of use, and performance to usage intention. The TAM relationships were mostly confirmed, except ease of use to usefulness. Usage intention was mostly determined by attitude, which was largely influenced by design, performance, and usefulness, and limitedly contributed by aesthetics and usefulness. Research limitations/implications: Participants' response might be influenced by the provided materials of 3D-printed apparel. Practical implications: The present study explicitly showed a complete picture about all possible influences among factors. Business managers can make strategies to meet consumers' needs based on the current study without worrying about overlooking any possible effects. Originality/value: The current study, for the first time, examined: consumers' adoption intention of 3D-printed apparel, the relationships among external variables, and how external factors comprehensively influenced consumers' perceptions, attitude, and usage intention.